2006
DOI: 10.1080/01674820500245638
|View full text |Cite
|
Sign up to set email alerts
|

Effects of genital prolapse surgery on sexuality

Abstract: Satisfaction about sexuality increases and the prevalence of sexual problems decreases in patients undergoing surgical correction of descensus uteri.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 20 publications
4
20
2
2
Order By: Relevance
“…The limited data on vaginal or open abdominal prolapse operations are controversial and are only partly in agreement with our findings [18][19][20][21]. Pauls et al [20] found that although the reasons sexually active patients report to be the cause of their sexual impairment change, the functionality and frequency of sexual intercourse are similar before and after vaginal prolapse and incontinence surgery.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…The limited data on vaginal or open abdominal prolapse operations are controversial and are only partly in agreement with our findings [18][19][20][21]. Pauls et al [20] found that although the reasons sexually active patients report to be the cause of their sexual impairment change, the functionality and frequency of sexual intercourse are similar before and after vaginal prolapse and incontinence surgery.…”
Section: Discussionsupporting
confidence: 78%
“…The discrepancy between the aforementioned finding and ours may be related to the relatively short, 6-month follow-up time used by Pauls et al [20]. Roovers et al [18] found a significantly elevated rate of general sexual satisfaction 1 year after vaginal or open (abdominal) prolapse surgery. In contrast, Jeng et al [19] described a significantly reduced frequency of postoperative orgasm in 20%, but no change in other sexual functions.…”
Section: Discussioncontrasting
confidence: 52%
“…Following this, recent studies have reported dyspareunia rates to be between 13 and 20% [22,23]. Coversely, some authors have reported an improvement in the sexual satisfaction and a decrease in sexual problems following pelvic organ prolapse surgery [24]. In one study, sexual function and satisfaction improved or did not change in most women after surgery for either prolapse or urinary incontinence, or both [25].…”
Section: Gynecological Cosmetic Surgerymentioning
confidence: 91%
“…Concernant la voie haute, trois é tudes plus ré centes [28][29][30] ont toutes utilisé des questionnaires validé s sur la sexualité . Il s'agit d'é tudes prospectives qui observent dans deux cas une amé lioration de la sexualité aprè s chirurgie et pas ou peu de modifications dans l'autre cas [28].…”
Section: Sexualiteńunclassified
“…Il s'agit d'é tudes prospectives qui observent dans deux cas une amé lioration de la sexualité aprè s chirurgie et pas ou peu de modifications dans l'autre cas [28].…”
Section: Sexualiteńunclassified